The Ukraine Support Tracker: Which countries help Ukraine and how? - Arianna Antezza; André Frank; Pascal Frank; Lukas Franz; Ekaterina Rebinskaya; Christoph Trebesch (Kiel Institute for the World Economy (IfW Kiel), 2022)
This paper presents the 'Ukraine Support Tracker', which lists and quantifies military, financial and humanitarian aid to Ukraine in the context of the Russia-Ukraine war. This fourth version covers government commitments made between January 24 and June 7, 2022 and has a new detailed overview on weapon deliveries. We track support by 37 governments, including all G7 and European Union member countries, plus by EU institutions (thus including 38 donors). Private donations and aid through non-governmental organizations are not included due to a lack of systematic data, but we do show estimates on government costs of hosting Ukrainian refugees. To value in-kind support like military equipment or foodstuff, we rely on government statements as well as own calculations using market prices. We find significant differences in the scale of support across countries, both in absolute terms and as percent of donor country GDP. In billions of Euros, by far the largest bilateral supporter of Ukraine is the United States, followed by the EU institutions, the United Kingdom, and Germany. In percent of donor GDP, Eastern European countries stand out as particularly generous, and this is even more so once we account for refugee costs. Importantly, we now also document delays in aid delivery. Only about 17% of financial commitments have actually been disbursed to Ukraine. Moreover, some countries, like Germany or the US, have delivered less than half of the weapons they committed.
Additional information: This is the fourth version of the paper and database. We are continuously expanding, correcting, and improving this project and welcome any feedback and comments to ukrainetracker@ifw-kiel.de. We are greatly indebted to dozens of readers around the world who have sent us helpful comments and suggestions.; More recent version: http://hdl.handle.net/10419/262746
Keywords: F35; F51; H56; H63; H84; H81; 330; international aid; military aid; war; geoeconomics